The Effect of Direct and Indirect Non-Oil and Gas Taxes on Domestic Revenue in Timor Leste - Carlos Afonso BARRETO (International Journal of Environmental, Sustainability, and Social Science, 2020)
This study aims to determine the effect of direct and indirect non-oil taxes on domestic revenues. Secondary data are obtained from the tax office or the East Timor Revenue Service (ETRS). To determine the effect of direct and indirect non-oil and gas taxes on domestic revenues in Timor Leste, multiple regressions are used. Testing the Multiple Regression Hypothesis using the t test. The results obtained are that the non-oil and gas tax variable directly and has no positive effect on the state revenue variable. The results of the study show that direct and indirect non-oil and gas taxes together have an effect on the state revenue variable. From the regression equation, the results obtained from the effect of direct non-oil taxes on domestic revenues are $ 2,667. Meanwhile, the indirect non-oil and gas tax on domestic revenues was $ 1,525.